Studies of the energy dependence of diboson polarization fractions and the radiation-amplitude-zero effect in WZ production with the ATLAS Detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Sanfilippo, Lorenzo; Schöning, André; Schultz-Coulon, Hans-Christian; et al. (Physical review letters, 2024)
This Letter presents the first study of the energy dependence of diboson polarization fractions in 𝑊⁢𝑍→ℓ⁡𝜈⁢ℓ′⁡ℓ′⁡(ℓ,ℓ′=𝑒,𝜇) production. The dataset used corresponds to an integrated luminosity of 140 fb−1 of proton-proton collisions at a center-of-mass energy of 13 TeV recorded by the ATLAS detector. Two fiducial regions with an enhanced presence of events featuring two longitudinally polarized bosons are defined. A nonzero fraction of events with two longitudinally polarized bosons is measured with an observed significance of 5.3 standard deviations in the region with 100<𝑝𝑍𝑇≤200 GeV and 1.6 standard deviations in the region with 𝑝𝑍𝑇 >200 GeV, where 𝑝𝑍𝑇 is the transverse momentum of the 𝑍 boson. This Letter also reports the first study of the radiation-amplitude-zero effect. Events with two transversely polarized bosons are analyzed for the Δ⁢𝑌⁡(ℓ𝑊⁢𝑍) and Δ⁢𝑌⁡(𝑊⁢𝑍) distributions defined respectively as the rapidity difference between the lepton from the 𝑊 boson decay and the 𝑍 boson and the rapidity difference between the 𝑊 boson and the 𝑍 boson. Significant suppression of events near zero is observed in both distributions. Unfolded Δ⁢𝑌⁡(ℓ𝑊⁢𝑍) and Δ⁢𝑌⁡(𝑊⁢𝑍) distributions are also measured and compared to theoretical predictions.
ATLAS Collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, L. Sanfilippo, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, L. Vigani, M. Wessels, J. Zinsser [und zahlreiche weitere]
Gesehen am 14.01.2026